x + x2 = 6
So x2 + x - 6 = 0
x2 + 3x - 2x - 6 = 0
x(x + 3) - 2(x + 3) = 0
(x + 3)(x - 2) = 0
So x + 3 = 0 so that x = -3
or x - 2 = 0 so that x = 2
6 to the negative 2nd means that it equals 1 over 6 to the negative 2nd.
8=6+b2b=4
46
6+1 equals 7. Plus 3 equals 10. Plus 4 equals 14.
2.5 plus 6 plus 3 equals 2.5 plus 6 plus 3
6 to the negative 2nd means that it equals 1 over 6 to the negative 2nd.
8=6+b2b=4
No.
676
No! It equals 15, but 9-6=3.
46
6+1 equals 7. Plus 3 equals 10. Plus 4 equals 14.
2.5 plus 6 plus 3 equals 2.5 plus 6 plus 3
6 plus 7 plus 8 equals 6 plus 8 plus 7, what property is that?That is the associative property.
(6 plus 6) divided by (6 plus 6) times 6 equals 6
6.
28